DEMOCRACY "CHARACTER" LOCAL WISDOM BUILDING DEMOCRATIC POLITICAL AWARENESS OF CHARACTER “AKAL BUDI” AUTENTIK INDONESIA: A STUDY FROM EXPERIENCE OF GOVERNANCE SYSTEM OF REPUBLIC OF NAGARI IN WEST SUMATERA - Wendra Yunaldi (UNTAG Law Review, 2018)
Although democracy has become the icon of the world, democracy still has the potential to accommodate in itself the values that are of national locality. Thevalues then make democracy different from one country to another. There is a tendency to strengthen the role of the state by reducing the role of popular sovereignty, the development of democracy in the end tends to face the interests of the people themselves. Democracy is no longer a symbol of power politics in favor of the people.In order to maintain the consistency and content of morality or character in democracy, the values of indigenous peoples, such as Nagari which develops musyawarah, togetherness, control, supervision, togetherness, etc., have the potential to encourage the realization of an authentic and authentic Indonesian democratic system. Although institutionally, the development of institutional model of democracy has been good enough, but the institution or organization can not be separated from the substantial values that will lead and at the same time keep it running in the corridor of democracy.Because, the strong tendency of power tends to corrupt and abuse of power, then the values of morality that became the character of Indonesia should be affirmed in the democratic system adopted by the Indonesian nation today. Thus, the goal of realizing a politically just social life for all Indonesian people can be realized.